The Impact of Global Human Rights Advocacy on State Practices: A Multi-Country Study - Feibe Engeline Pijoh (Eastasouth Institute, 2023)
This study investigates the influence of international human rights advocacy on state practices in Indonesia and Malaysia. The research uses a mixed methods approach, combining quantitative analysis of human rights indicators and qualitative analysis of case studies and interviews. The findings show successes and challenges in the relationship between advocacy efforts and state behavior in both countries. The quantitative analysis shows improvements in certain areas, such as gender equality in Indonesia and legislative reform in Malaysia, while challenges remain in terms of freedom of expression, religious freedom, and minority rights. The qualitative analysis provides deeper insights, highlighting the important role of advocacy in raising awareness, promoting accountability, and pressuring governments to address human rights violations. However, barriers to effective implementation exist due to political resistance and societal divisions. A comparative analysis between Indonesia and Malaysia shows similarities and differences, with Indonesia showing a greater response to reform and Malaysia showing resistance that limits freedoms. This research contributes to the field by emphasizing the need for context-specific analysis and tailored approaches to address human rights challenges.